Appraisal of Human Resource Management in Georgian Public Service: Quantitative Research - Nino Sardlishvili (European Scientific Journal, ESJ, 2021)
The ongoing reforms in the Georgian public sector are crucial for the future development of this field, as waves of reforms systematically increase the efficiency of the sector. The attitude of people employed in the public sector is decisive towards the ongoing reforms and is considered to be essential and interesting at the same time. Quantitative research was conducted using electronic questionnaires to examine the position of public sector employees. The research has shown that working in the public sector is very popular and the main reason for this popularity is for stability. Another interesting thing is the fact that public servants are actively involved in activities planned and implemented by their employer. Although despite their readiness, a large number of public servants are skeptical about the ongoing processes.